Excitonic Creation of Highly Luminescent Defects In Situ in Working Organic Light‐Emitting Diodes. Issue 2 (21st December 2017) - Zhao, Yong‐Biao; Ingram, Grayson L.; Gong, Xi‐Wen; Li, Xi‐Yan; Quan, Li‐Na; Li, Pei‐Cheng; Xie, Jia‐Qi; Sargent, Edward H.; Lu, Zheng‐Hong
Abstract: Excitons play the central role in organic optoelectronic devices. Efficient exciton‐to‐photon and photon‐to‐electron conversion promote quantum yield in optoelectronic devices such as organic light‐emitting diodes and organic solar cells. Exciton‐related reaction products and defects in working devices have previously been viewed as fatal to stability. Here, the utilization of these excitonic reactions to create luminescent defects with extremely high (6.7%) external quantum efficiency in an operating device containing 1, 1‐bis((di‐4‐tolylamino)phenyl) cyclohexane (TAPC) is reported. Transient photoluminescence reveals a long delayed fluorescence lifetime (2.7 µs) from these emissive defects, indicating that they exhibit thermally activated delayed fluorescence. It is shown that the functional group of tri‐ p ‐tolylamine (TPTA) follows similar processes as TAPC, suggesting that the chemical nature of the observed luminescent defects is directly related to TPTA. Abstract : Excitonic processes in working organic light‐emitting diodes are engineered to produce extremely highly luminescent thermally activated delayed fluorescence defects with extremely high (>18 cd A −1 ) current efficiencies.